Recognition of anxiety disorders in children: a cross-sectional vignette-based survey among general practitioners - Mattijs E Numans; Semiha Aydin; Mathilde R Crone; Bart M Siebelink; Robert R J M Vermeiren; P Michiel Westenberg (BMJ Open)
Objective To quantify general practitioners’ (GPs) sensitivity to anxiety disorders (ADs) when confronted with the range of symptoms common to children with ADs. Also, to explore GPs’ conscious preferences and implicit tendencies for referral of children with ADs to mental healthcare.Design and setting In a cross-sectional vignette-based survey, all attendees of a Dutch continuing medical education conference for primary care physicians were presented with subtitled audio fragments of five vignettes that we constructed to mimic symptom presentation of children with ADs in general practice. We asked attendees to select per vignette the most plausible diagnoses and most adequate referral option, and for their general referral preferences when they suspect each of the most common mental health problems.Participants A sample of 229 GPs, resulting in a total of 1128 vignette evaluations.Main outcome measure GPs’ selection rate of ADs in the five vignettes compared with a benchmark provided by mental health professionals (MHPs).Results Overall, recognition of ADs was less likely in GPs compared with MHPs (OR=0.26, 95% CI 0.15 to 0.46). GPs varied in their recognition of anxiety, with 44.1% not once selecting anxiety as the probable presenting problem. When asked explicitly, 63.9% of the GPs reported that they would refer a child to mental healthcare when they suspect probable ADs. By contrast, only 12.0% of the GPs who recognised anxiety in the vignettes actually selected that referral option.Conclusion A significant fraction of GPs did not notice the depicted symptoms as anxiety. Despite the widespread prevalence of ADs, GPs seem to overlook anxiety already in their early diagnostic opinion. Improving GPs’ familiarity with initial symptom presentation, ADs’ base-rate, relevance and impact yields potential for timely recognition.